A low-cost, portable, and practical LAMP device for point-of-diagnosis in the field - Vural Kaymaz, Sümeyra; Ergenç, Ali F.; Aytekin, Ali Ö.; Lucas, Stuart J.; Elitas, Meltem (Wiley, 2021)
Transition of rapid, ready-to-use, and low-cost nucleic acid-based detection technologies from laboratories to points of sample collection has drastically accelerated. However, most of these approaches are still incapable of diagnosis starting from sampling, through nucleic acid isolation and detection in the field. Here, we developed a simple, portable, low-cost, colorimetric, and remotely controllable platform for reliable, high-throughput, and rapid diagnosis using loop mediated isothermal amplification (LAMP) assays. It consists of a thermally isolated cup, low-cost electronic components, a polydimethylsiloxane sample well, and a fast prototyped case that covers electronic components. The steady-state temperature error of the system is less than 1%. We performed LAMP, Colony-LAMP, and Colony PCR reactions using the yaiO2 primer set for Escherichia coli and Pseudomonas aeruginosa samples at 65˚C and 30 min. We detected the end-point colorimetric readouts by the naked eye under day light. We confirmed the specificity and sensitivity of our approach using pure genomic DNA and crude bacterial colonies. We benchmarked our Colony-LAMP detection against Colony PCR. The number of samples tested can easily be modified for higher throughput in our system. We strongly believe that our platform can greatly contribute rapid and reliable diagnosis in versatile operational environments.
Keywords: Pseudomonas aeruginosa; Escherichia coli; Colorimetry; Nucleic Acid Amplification Techniques; Polymerase Chain Reaction; Sensitivity and Specificity